Value of pre-treatment biomarkers in prediction of response to neoadjuvant endocrine therapy for hormone receptor-positive postmenopausal breast cancer - Ying, Min; He, Yingjian; Qi, Meng; Dong, Bin; Lu, Aiping; Li, Jinfeng; Xie, Yuntao; Wang, Tianfeng; Lin, Benyao; Ouyang, Tao (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To determine the predictive ability of biomarkers for responses to neoadjuvant endocrine therapy (NET) in postmenopausal breast cancer. Methods: Consecutive 160 postmenopausal women with T1-3N0-1M0 hormone receptor (HR)-positive invasive breast cancer were treated with anastrozole for 16 weeks before surgery. New slides of tumor specimens taken before and after treatment were conducted centrally for biomarker analysis and classified using the Applied Imaging Ariol MB-8 system. The pathological response was evaluated using the Miller & Payne classification. The cell cycle response was classified according to the change in the Ki67 index after treatment. Multivariable logistic regression analysis was used to calculate the combined index of the biomarkers. Receiver operating characteristic (ROC) curves were used to determine whether parameters may predict response. Results: The correlation between the pathological and cell cycle responses was low (Spearman correlation coefficient =0.241, P